Video as a technique to improve the pronunciation of present tense of verbs in third person singular and its effects in 10th B graders at Daniel O. Crespo High School - Morales Villarreal, Deyvis Alberto (David, Panamá : UDELAS, 2014)
The pronunciation in a language is essential to understand more easily the message. English language is characterized by emission of different sounds as they are often very difficult to pronounce for studends studying this language . This project comprise four chapters where all the research on the pronunciation of the morpheme -s in the third person singular and videos as a technique breaks down to facilitate this learning.
TABLE OF CONTENTS CHART INDEX GRAPHIC INDEX INTRODUCTION CHAPTER I: ANTECEDENTES AND STATEMENTS OF THE PROBLEM 1.1. Antecedents 1.2. Statement of the problem 1.2.1. Descriptions and formulation of the problem 1.2.2. Formulation of the problem 1.3. Justification 1.4. Objectives 1.4.1. General objetive (s) 1.4.2. Specific objetives 1.5. Scope and delimitation 1.5.1. Scope 1.5.2. Delimitation CHAPTER II: THEORETICAL FRAMEWORK 2.1. Pronunciation 2.1.1. Definition 2.1.1.1. Sound production 2.1.1.2. Suprasegmentals aspects of pronunciation 2.1.2. Pronunciation problems 2.1.2.1. Pronunciation of vowels 2.1.2.2. Pronunciation of consonants 2.2. Morphology 2.2.1. Definition 2.2.2. Types of morphemes 2.2.2.1. Free morphemes 2.2.2.2. Bound morphemes 2.2.3. Word formation 2.3. The "s" of third person singular in the present simple 2.3.1. Definición 2.3.2. Morphophonemic rules of sound "s" in third person singular in verbs in present tense 2.3.3. Mispronunciation in third person singular 2.4. Techinique to teaching pronunciation 2.4.1. Techniques 2.4.2. Types of technologies resourses 2.4.2.1. Recordings 2.4.2.2. Videos 2.4.3. Types of techniques 2.4.3.1. Classic oral repeated reading technique 2.4.3.2. Video modeling CHAPTER III: METHODOLOGICAL ASPECTS 3.1. Type of research 3.1.1. Quantitative research 3.1.2. Descriptive research 3.1.3. Demographic research 3.2. Information sources 3.2.1. Human sources of information 3.2.2. Material sources of information 3.3.Subjects 3.4. Variable system 3.4.1. Variable 1 3.4.1.1. Conceptual definition 3.4.1.2. Operational definition 3.4.2. Variable 2 3.4.2.1. Conceptual definition 3.4.2.2. Operational definition 3.5. Description of data collection instruments 3.5.1. Closed questionnaire 3.5.2. Pronunciation proficiency test 3.6. Treatment of information CHAPTER IV: ANALYSIS AND RESULTS 4.1. Chart to analyze the results obtained from the pretest 4.2. Descriptive analysis CONCLUSIONS RECOMMENDATIONS BIBLIOGRAPHY ANNEX
Incluye Table of contents
Incluye Annex
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés.
Incluye Bibliografía
No se presta a domicilio.
No se saca fotocopias.
Keywords: ENGLISH -- TESIS; INGLÉS -- TESIS; GRAMMAR -- TESIS -- ENGLISH; ENGLISH -- TESIS -- VERBS; LICENCIATURA EN DOCENCIA EN INGLÉS - TESIS; DANIEL OCTAVIO CRESPO; PRONUNCIATION OF VERBS - VIDEOS